2017
DOI: 10.1002/ecy.1994
|View full text |Cite
|
Sign up to set email alerts
|

A historical perspective of nutrient change impact on an infectious disease in Daphnia

Abstract: Changes in food quality can play a substantial role in the vulnerability of hosts to infectious diseases. In this study, we focused on the genetic differentiation of the water flea Daphnia magna towards food of different quality (by manipulating C:N:P ratios) and its impact on the interaction with a virulent infectious disease, "White Fat Cell Disease (WFCD)". Via a resurrection ecology approach, we isolated two Daphnia subpopulations from different depths in a sediment core, which were exposed to parasites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
(195 reference statements)
0
7
0
Order By: Relevance
“…The multi-faceted aspect of eutrophication on freshwater foodwebs and species interactions has been addressed by coupling resurrected Daphnia with bacterial infections (Pasteuria ramosa) against a background of changing food quality associated with increased nutrient load. Reyserhove et al 52 show that genetic differentiation in Daphnia is affected by food availability, and ultimately influences parasite virulence. Finally, an example from the marine realm: as described earlier, resting stages of the dinoflagellate Pentapharsodinium dalei can survive ca.…”
Section: Strengths Weaknesses Referencesmentioning
confidence: 99%
“…The multi-faceted aspect of eutrophication on freshwater foodwebs and species interactions has been addressed by coupling resurrected Daphnia with bacterial infections (Pasteuria ramosa) against a background of changing food quality associated with increased nutrient load. Reyserhove et al 52 show that genetic differentiation in Daphnia is affected by food availability, and ultimately influences parasite virulence. Finally, an example from the marine realm: as described earlier, resting stages of the dinoflagellate Pentapharsodinium dalei can survive ca.…”
Section: Strengths Weaknesses Referencesmentioning
confidence: 99%
“…These and other types of anthropogenic change may lead to spatial or temporal mismatches between antagonists, resulting in host shifts and the rapid spread of disease across susceptible host populations not historically exposed to particular pathogens (Penczykowski et al, 2016). For instance, an increased level of eutrophication (i.e., nutrient "pollution") in time can lead to increased pathogen prevalence and virulence, which may promote evolution toward elevated virulence (Aalto, Decaestecker, & Pulkkinen, 2015;Decaestecker et al, 2007;Forde, Thompson, & Bohannan, 2004;Johnson et al, 2010 (Aalto et al, 2015;Reyserhove et al, 2017). Together, the analyses of stratified egg banks are a key instrument to link evolutionary dynamics in natural populations with environmental change (Frisch et al, 2013(Frisch et al, , 2016Hairston et al, 1999Hairston et al, , 2001.…”
Section: Virulence Evolution In Resurrected Host-pathogen Interactionsmentioning
confidence: 99%
“…Lake sediments serve as archives of environmental change, where paleolimnological methods can be used to reconstruct changes in an elemental context (Bennion, Fluin, & Simpson, ; Battarbee, Anderson, Jeppesen, & Leavitt, ; see Burge et al., this issue). It is estimated that if environmental nutrient enrichment or increased temperature is translated into higher population sizes, then increased host–pathogen interactions, in terms of within‐host competition and pathogen transmission, may intensify the coevolutionary arms race and virulence outcome between hosts and pathogens (Aalto et al., ; Reyserhove et al., ). Together, the analyses of stratified egg banks are a key instrument to link evolutionary dynamics in natural populations with environmental change (Frisch et al., , ; Hairston et al., , ).…”
Section: Research Avenues Of Resurrection Ecologymentioning
confidence: 99%
“…Zooplankton, for example, have been found to be negatively affected by both the relative limitation or excess of either N or P in their food resources (Boersma & Elser , Zhou and Declerck ). For instance, a high phytoplankton N : P ratio can serve as low quality food for zooplankton due to relative excess of nitrogen (Reyserhove et al , b ), or limitation by phosphorus (Andersen and Hessen ; Sterner et al ; Acharya et al ; Zhou et al ).…”
mentioning
confidence: 99%
“…In particular, we studied how phytoplankton N : P ratio impacts Daphnia epibiont prevalence, association intensity, and species richness in natural Daphnia populations and in experimental Daphnia cohorts. We focus on this food quality variable as it is particularly relevant in the context of increasing N to P supply rates to aquatic ecosystems (Peñuelas et al , 2013) and as nutrient availability (both N and P) have been suggested to impact Daphnia – endoparasite interactions (Aalto et al ; Reyserhove et al , b ; Narr et al ). We expect that the effect of stoichiometric imbalance in the elemental supply of the environment will have an effect on the species composition and relative abundance of the epibionts.…”
mentioning
confidence: 99%